Chronic pelvic pain in a postmenopausal patient with a forgotten Lippes loop: a case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2017)
Introduction: A calcified endometrial mass is a worrying finding in a postmenopausal patient, warranting urgent  intervention. This case highlights an interesting presentation of a Lippes loop that has grown into an endometrial  polyp, raising suspicion that it may have been a malignancy.  Case presentation: This is a case of a 70 year old multiparous patient who presented with history of chronic pelvic  pain. She could not recall insertion of the Lippes loop, and had therefore never sort to have it removed.  Management and outcome: The patient underwent total abdominal hysterectomy and bilateral salpingo oophorectomy. She made a complete recovery, and histology revealed a calcified endometrial polyp. Conclusion: The Lippes loop is no longer inserted and is becoming a rare find in the practice of gynaecology. This  case was an usual presentation of a Lippes loop, as the endometrial polyp had grown around the Lippes loop giving  the impression of a calcified endometrial lesion.